Biochemical characterization of an azoreductase from Rhodococcus opacus 1CP possessing methyl red degradation ability - Qi, Jingxian; Schlömann, Michael; Tischler, Dirk (Journal of molecular catalysis. B, Enzymatic, 2016)
[Display omitted] •Rhodococcus opacus 1CP grows on methyl red.•First azoreductase annotated and described of rhodococci.•Oxygen-insensitive and stable azoreductase.•Classification of azoreductases according to sequence and biochemical properties. Azo dyes, characterized by one or more R1NNR2 bonds, could be enzymatically metabolized. A flavin-containing oxygen-insensitive azoreductase designated as AzoRo (25KDa) from strain Rhodococcus opacus 1CP was identified and catalyses the initial degradation step of azo dyes. Protein sequence of AzoRo shared best identity of 33% to PaAzo1 from Pseudomonas aeruginosa for which the structure was solved, but clearly forms an own branch in the dendrogram. Thus AzoRo seems to be another subtype of azoreductases. The optimized gene coding for AzoRo of 214 amino acids was heterologously expressed in Escherichia coli BL21 (DE3). NADH served as an electron donor and a typical azo dye 2-(4-dimethylaminophenylazo) benzoic acid (methyl red) served as the substrate. The apparent kinetic values Km and Vmax of NADH are 10.07μM and 51.48U/mgprotein. Effect properties including pH, temperature and metal ions were characterized. Results showed AzoRo performed higher degradation velocity between pH 3.8–5 in acetate buffer. But, it would not be stable in that pH range. The thermal assay revealed the optimal temperature is 53°C. AzoRo remained stable from 10 to 40°C. However, the unfolding temperature is 55°C. RPHPLC analysis verified the products through AzoRo cleavage of methyl red. AzoRo is the first azoreductase obtained from a Rhodococcus strain which has been described in detail after initial biochemical characterization.